Conductive paint and printed wiring board
The conductive paint formulation, featuring a specific blend of binder resin, crosslinker, carbon black, and conductive filler, addresses the issue of resistance change in stretched coating films, providing a durable and reliable solution for flexible electronic devices.
Patent Information
- Application Number
- JP2023026058
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2043-02-22
AI Technical Summary
Conductive paints used in flexible devices experience a significant increase in resistance value when the coating film stretches, especially when the initial resistance is low, leading to noticeable changes in resistance after expansion and contraction.
A conductive paint formulation comprising a binder resin with a weight average molecular weight of 200 to 7,000, a crosslinker, carbon black with a dibutyl phthalate oil absorption amount of 100-600ml/100g, and a conductive filler, in specific mass ratios, to form a coating film with minimal resistance change upon stretching.
The proposed conductive paint and printed wiring board combination achieves a small change in resistance value after stretching, even with low initial resistance, ensuring durability and reliability in flexible electronic applications.
Smart Images

Figure 0007648921000001 
Figure 0007648921000002 
Figure 0007648921000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive paint and a printed wiring board. [Background technology]
[0002] In recent years, efforts have been actively made to popularize devices that require flexibility and stretchability, such as wearable devices, flexible printed circuit boards, displays, etc. These devices are usually formed by applying a conductive paint containing conductive particles and a binder resin onto a flexible and stretchable substrate, but the coating film formed from the conductive paint may also be required to have stretchability. As an example of a conductive component with elastic wiring, Patent Document 1 discloses a conductive component having wiring formed by drying a conductive paste of polyurethane dispersion and conductive particles, and a plastic substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-54192 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the resistance of a coating film formed from a conventional conductive paint increases when it is stretched repeatedly, and the rate of change in the resistance after stretching relative to the resistance before stretching (initial resistance) may become large. In particular, when the initial resistance is low, the change in resistance when the resistance after stretching increases tends to be significant. An object of the present invention is to provide a conductive paint and a printed wiring board which are capable of forming a coating film in which the change in resistance value after expansion and contraction is small even when the initial resistance value is low. [Means for solving the problem]
[0005] The present invention has the following aspects. [1] A binder resin (A), a crosslinking agent (B), carbon black (D), and a conductive filler (C) other than the carbon black (D), the carbon black (D) has a dibutyl phthalate oil absorption of 100 to 600 ml / 100 g; The binder resin (A) contains a resin having a weight average molecular weight of 200 to 7,000, a mass ratio (A+B) / C of the total content of the binder resin (A) and the crosslinking agent (B) to the content of the conductive filler (C) is 5 / 95 to 35 / 65; the content of the carbon black (D) is 0.5 to 3.5 parts by mass relative to 100 parts by mass of the total content of the binder resin (A), the crosslinking agent (B), and the conductive filler (C); A conductive paint that satisfies the following formula (1). DBP oil absorption × Wd / Wab≦130 (1) (In formula (1), "DBP oil absorption" is the dibutyl phthalate oil absorption of carbon black (D), "Wd" is the content of carbon black (D) relative to 100 parts by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C), and "Wab" is the total content of binder resin (A) and crosslinking agent (B) in 100% by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C).) [2] A printed wiring board having a circuit formed on an insulating substrate by a coating film obtained by using the conductive paint according to [1] above. Effect of the Invention
[0006] According to the present invention, it is possible to provide a conductive paint and a printed wiring board capable of forming a coating film in which the change in resistance value after expansion and contraction is small even when the initial resistance value is low. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The following definitions of terms apply throughout the specification and claims. The term "conductive" is a term that is distinguished from the general meaning of "insulating", and with respect to a circuit pattern, it preferably means that the electrical resistance value is less than 150 Ω. The "coating film" refers to a coating film formed from the conductive coating material of the present invention, and is also called a "conductive coating film" or a "cured coating film." The symbol "~" indicating a range of numerical values means that the numerical values before and after it are included as the lower limit and upper limit.
[0008] [Conductive paint] The conductive coating material of the present invention contains the following binder resin (A), crosslinking agent (B), carbon black (D), and conductive filler (C) other than carbon black (D). The conductive paint may further contain components other than the binder resin (A), the crosslinking agent (B), the conductive filler (C) and the carbon black (D) (hereinafter also referred to as "other components") as necessary, as long as the effects of the present invention are not impaired.
[0009] <Binder resin (A)> The binder resin (A) may be any resin that acts as a binding resin for the conductive coating material, and is preferably one having a reactive group. Examples of the reactive group include a hydroxyl group, an amino group, an amide group, an imino group, a carboxyl group, a carbonyl group, an epoxy group, an isocyanate group, an alkyl ether group, a hydrazide group, a mercapto group, a vinyl group, a methacryl group, and an acryl group.
[0010] Examples of the binder resin (A) include polyol resins, polyester resins, polyurethane resins, phenoxy resins, polyamide resins, polyamideimide resins, polyimide resins, polyurea resins, acrylic resins, epoxy resins, polystyrene, styrene-acrylic resins, styrene-butadiene copolymers, epoxy resins, phenolic resins, vinyl resins, polyether resins, polycarbonate resins, alkyd resins, polysulfone resins, polyethersulfone resins, vinyl chloride-vinyl acetate copolymer resins, ethylene-vinyl acetate copolymers, silicone resins, fluorine-based resins, etc. Among these, polyol resins are preferred from the viewpoint of improving the elasticity of the coating film. The binder resin (A) may be used alone or in combination of two or more. However, the binder resin (A) contains at least a resin having a weight average molecular weight of 200 to 7,000. In particular, the binder resin (A) preferably contains a polyol resin (hereinafter also referred to as "binder resin (A1)") having a weight average molecular weight of 200 to 7,000, and more preferably contains the binder resin (A1) and a resin other than the binder resin (A1) (hereinafter also referred to as "binder resin (A2)").
[0011] (Binder resin (A1)) The binder resin (A1) is a polyol resin having a weight average molecular weight of 200 to 7,000. The polyol resin has a hydroxyl group (-OH) that reacts with the isocyanate group (-NCO) of the isocyanate compound, and is not particularly limited as long as it has a weight average molecular weight of 200 to 7,000. Examples of the polyol resin include polyester polyol, acrylic polyol, polyether polyol, polycarbonate polyol, polycaprolactone polyol, polyolefin polyol, epoxy polyol, polyurethane polyol, etc. Among these, polyester polyol and polycarbonate polyol are preferred. The polyol resin may be used alone or in combination of two or more kinds.
[0012] The polyester polyol and the polycarbonate polyol are each a reaction product of a polybasic acid and a polyhydric alcohol, etc. The polyester polyol and the polycarbonate polyol contained in the binder resin (A1) may each be one type or two or more types.
[0013] Examples of polybasic acids include ethylenically saturated polycarboxylic acids such as phthalic anhydride, phthalic acid, terephthalic acid, isophthalic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, succinic acid, citraconic acid, adipic acid, and sebacic acid; and ethylenically unsaturated polycarboxylic acids such as maleic anhydride, maleic acid, itaconic anhydride, itaconic acid, fumaric acid, endomethylenetetrahydrophthalic anhydride, and endomethylenetetrahydrophthalic acid. The polybasic acids may be used alone or in combination of two or more kinds.
[0014] Examples of polyhydric alcohols include polyether polyols such as diethylene glycol, dipropylene glycol, triethylene glycol, and polyethylene glycol, polyester polyols, ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-pentanediol, neopentyl glycol, 1,6-hexanediol, cyclohexanediol, 2,2,4-trimethyl-1,3-pentanediol, 3-methyl-1,5-pentanediol, glycerin, glycerin monoallyl ether, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.
[0015] The hydroxyl value of the binder resin (A1) is preferably 5 mgKOH / g or more, more preferably 10 mgKOH / g or more, and even more preferably 15 mgKOH / g or more. The hydroxyl value of the binder resin (A1) is preferably 750 mgKOH / g or less, more preferably 500 mgKOH / g or less, and even more preferably 250 mgKOH / g or less. When the hydroxyl value of the binder resin (A1) is within the above range, the coating film has good stretchability. The upper and lower limits of the hydroxyl value of the binder resin (A1) can be arbitrarily combined. For example, the hydroxyl value of the binder resin (A1) is preferably from 5 to 750 mgKOH / g, more preferably from 10 to 500 mgKOH / g, and even more preferably from 15 to 250 mgKOH / g.
[0016] The hydroxyl value of the binder resin (A1) is measured by a method conforming to JIS K 0070:1992 "Testing methods for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemical products". For those with catalog values, the catalog values may be used as a simplified measured value for the hydroxyl value of the binder resin (A1).
[0017] The weight average molecular weight of the binder resin (A1) is 200 or more, preferably 350 or more, and more preferably 500 or more. When the weight average molecular weight of the binder resin (A) is equal to or more than the lower limit, an excessive increase in thixotropy can be suppressed, and a smooth coating film can be easily obtained. In addition, since excessive crosslinking can be suppressed, the adhesion of the coating film to the substrate is improved. The weight average molecular weight of the binder resin (A1) is 7,000 or less, preferably 6,500 or less, more preferably 6,000 or less. If the weight average molecular weight of the binder resin (A1) is equal to or less than the upper limit, the stretchability of the coating film is improved and the change in resistance value after stretching is smaller. In addition, the adhesion of the coating film to the substrate is improved. The upper and lower limits of the weight average molecular weight of the binder resin (A1) can be combined in any desired manner. For example, the weight average molecular weight of the binder resin (A1) is 200 to 7,000, preferably 350 to 6,500, and more preferably 500 to 6,000.
[0018] The weight average molecular weight of the binder resin (A1) is a value measured by gel permeation chromatography (GPC) and converted into standard polystyrene. If a catalog value is available, the catalog value may be used as a simple measurement value for the weight average molecular weight of the binder resin (A1).
[0019] The glass transition temperature of the binder resin (A1) is preferably −100 to 0° C., more preferably −90 to 0° C., and even more preferably −85 to 0° C. When the glass transition temperature of the binder resin (A1) is within the above range, the elasticity and durability of the coating film are further improved.
[0020] The glass transition temperature of the binder resin (A1) is measured by a method conforming to JIS K 7121:2012 "Method of measuring glass transition temperature of plastics." If a catalog value is available, the catalog value may be used as a simple measured value for the glass transition temperature of the binder resin (A1).
[0021] The polyester polyol and the polycarbonate polyol may each be a commercially available product, and examples of such products include those available from Kuraray Co., Ltd. under the trade names "Kuraray Polyol P-2010," "Kuraray Polyol P-510," "Kuraray Polyol P-6010," "Kuraray Polyol C-590," "Kuraray Polyol C-1090," "Kuraray Polyol C-2090," and "Kuraray Polyol C-3090."
[0022] (Binder resin (A2)) The binder resin (A2) is a binder resin other than the binder resin (A1). As the binder resin (A2), among the binder resins (A) exemplified above, polyester resins and polyol resins having a weight average molecular weight of more than 7,000 are preferred from the viewpoint of improving the adhesion of the coating film to the substrate.
[0023] The polyester resin is a reaction product of a polybasic acid and a polyhydric alcohol. Examples of the polybasic acid and polyhydric alcohol include the polybasic acids and polyhydric alcohols exemplified above in the description of the binder resin (A1). The polyester resin contained in the binder resin (A2) may be one type or two or more types.
[0024] The hydroxyl value of the binder resin (A2) is preferably 1 mgKOH / g or more, and more preferably 2 mgKOH / g or more. The hydroxyl value of the binder resin (A2) is preferably 10 mgKOH / g or less, more preferably 7 mgKOH / g or less. When the hydroxyl value of the binder resin (A2) is within the above range, the elasticity of the coating film is further improved. The upper and lower limits of the hydroxyl value of the binder resin (A2) can be arbitrarily combined. For example, the hydroxyl value of the binder resin (A2) is preferably from 1 to 10 mgKOH / g, more preferably from 2 to 7 mgKOH / g.
[0025] The hydroxyl value of the binder resin (A2) can be measured in the same manner as the hydroxyl value of the binder resin (A1). If a catalog value is available, the catalog value may be used as a simple measurement value for the hydroxyl value of the binder resin (A2).
[0026] The weight average molecular weight of the binder resin (A2) is preferably 10,000 or more, more preferably 12,000 or more, further preferably 15,000 or more, and particularly preferably 20,000 or more. The weight average molecular weight of the binder resin (A2) is preferably 50,000 or less, more preferably 45,000 or less, further preferably 40,000 or less, particularly preferably 35,000 or less. When the weight average molecular weight of the binder resin (A2) is within the above range, the durability of the coating film is improved. The upper and lower limits of the weight average molecular weight of the binder resin (A2) can be combined in any combination. For example, the weight average molecular weight of the binder resin (A2) is preferably 10,000 to 50,000, more preferably 12,000 to 45,000, further preferably 15,000 to 40,000, and particularly preferably 20,000 to 35,000.
[0027] The weight average molecular weight of the binder resin (A2) can be measured in the same manner as the weight average molecular weight of the binder resin (A1). If a catalog value is available, the catalog value may be used as a simple measurement value for the weight average molecular weight of the binder resin (A2).
[0028] The glass transition temperature of the binder resin (A2) is preferably 30° C. or lower, more preferably 0 to 25° C. When the glass transition temperature of the binder resin (A2) is within the above range, the elasticity and durability of the coating film are further improved.
[0029] The glass transition temperature of the binder resin (A2) can be measured in the same manner as the glass transition temperature of the binder resin (A1). If a catalog value is available, the catalog value may be used as a simple measured value for the glass transition temperature of the binder resin (A2).
[0030] As the polyester resin, commercially available products may be used, for example, trade names "ELITEL UE-3220", "ELITEL UE-3223", "ELITEL UE-3400", "ELITEL UE-3500", "ELITEL UE-3510", "ELITEL UE-9100" manufactured by Unitika Ltd.
[0031] <Crosslinking agent (B)> The crosslinking agent (B) may be any agent that reacts with the reactive groups contained in the binder resin (A). Examples of the crosslinking agent (B) include amine-based crosslinking agents, epoxy-based crosslinking agents, isocyanate-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, ammonium salt-based crosslinking agents, etc. Among these, isocyanate-based crosslinking agents are preferred from the viewpoint of forming a coating film in which the change in resistance value is small even when stretched and contracted repeatedly. The crosslinking agent (B) may be used alone or in combination of two or more kinds.
[0032] Examples of the isocyanate crosslinking agent include methylene diisocyanate, isopropylene diisocyanate, butane-1,4-diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, hexamethylene diisocyanate (HDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), tolylene diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenylisocyanate. The isocyanate-based crosslinking agent may be used alone or in combination of two or more kinds.
[0033] <Conductive filler (C)> The conductive filler (C) imparts electrical conductivity to the coating film. The conductive filler (C) is not particularly limited as long as it is used in conductive paints and is other than carbon black (D) described below, and examples thereof include metals such as gold, silver, copper, platinum, and nickel; graphite, etc. The conductive filler (C) may be composed of two or more elements, for example, an alloy, a metal or a resin coated with the above-mentioned metals. Among these, metals other than silver or resins coated with silver are preferred. The conductive filler (C) may be used alone or in combination of two or more kinds. In this specification, the conductive filler (C) which is silver is also referred to as "silver powder" or "silver powder conductive filler".
[0034] The shape of the conductive filler (C) is not particularly limited as long as the desired conductivity is obtained. When the conductive filler (C) is silver, the shape may be, for example, a spherical, scaly, flat, plate-like, flaky, needle-like, rod-like, fibrous, lumpy, cubic, bead-like, irregular, or a shape with protrusions on the surface like candy cane. The average thickness of the flakes is usually 1 / 10 to 1 / 2 of the average particle size. In addition, "irregular" means that various shapes such as those listed above are mixed and the shape cannot be limited. Among these, flakes, spherical, lumpy, needle-like, and irregular shapes are preferred from the viewpoint of forming a coating film with a small change in resistance value after expansion and contraction. The conductive filler (C) contained in the conductive paint may be of one type of shape, but from the viewpoint of being able to form a coating film with smaller change in resistance value after stretching, it is preferable that the conductive paint contains conductive filler (C) of two or more different shapes.
[0035] The average particle size of the conductive filler (C) is preferably 7 μm or less, more preferably 1 to 7 μm, and even more preferably 2 to 5 μm. If the average particle size of the conductive filler (C) is equal to or less than the above upper limit, the conductive filler (C) has excellent printability when, for example, a coating film is formed by printing a conductive paint on a substrate. In addition, the conductive filler (C) has excellent conductivity when the coating film is formed from the conductive paint and excellent suppression of the change in conductivity when the conductive filler (C) is stretched or contracted. The average particle size of the conductive filler (C) is a value measured as follows. That is, the arithmetic mean diameter calculated from the volume distribution measured by a laser diffraction scattering type particle size distribution measurement method is taken as the average particle size of the conductive filler (C). Note that, for those with catalog values, the catalog values may be used as a simple measurement value for the average particle size of the conductive filler (C).
[0036] <Carbon black (D)> The dibutyl phthalate oil absorption (hereinafter also referred to as "DBP oil absorption") of carbon black (D) is 100 to 600 ml / 100 g, and preferably 120 to 500 ml / 100 g. When the DBP oil absorption of carbon black (D) is equal to or higher than the lower limit, the elasticity of the coating film is improved. When the DBP oil absorption of carbon black (D) is equal to or lower than the upper limit, good film formability can be maintained. The DBP oil absorption of carbon black (D) is the amount of dibutyl phthalate (DBP) required to fill the voids in a certain amount of carbon black (D), and is an index that represents the degree of development of the structure of carbon black (D). The DBP oil absorption of carbon black (D) is measured according to JIS K 6217-4:2017 "Carbon black for rubber - Basic properties - Part 4: Determination of oil absorption." For those with catalog values, the catalog values may be used as a simplified measurement value for the DBP oil absorption of carbon black (D).
[0037] Examples of the carbon black (D) include ketjen black, acetylene black, furnace black, and channel black. The carbon black (D) may be used alone or in combination of two or more kinds.
[0038] <Other ingredients> As other components, components that can be used in conventionally known conductive paints, such as solvents, dispersants, surface conditioners, thixotropic agents, adhesion promoters, resin modifiers, catalysts, coupling agents, non-conductive fillers, etc., can be used.
[0039] If the conductive paint contains a solvent, the viscosity can be easily adjusted. The solvent is preferably one capable of dissolving the binder resin (A), and examples thereof include organic solvents such as isophorone, terpineol, butyl diglycol acetate, and butyl acetate. The solvent may be used alone or in combination of two or more kinds.
[0040] <Content / mass ratio> The content of the resin having a weight average molecular weight of 200 to 7,000 relative to the total mass of the binder resin (A) is preferably 1 to 100 mass%, more preferably 1 to 50 mass%, further preferably 1 to 30 mass%, particularly preferably 3 to 20 mass%, and most preferably 5 to 15 mass%. If the content of the resin having a weight average molecular weight of 200 to 7,000 is within the upper range, even if the initial resistance value is low, it is likely to become a conductive coating material that can form a coating film with small change in resistance value after expansion and contraction.
[0041] When the binder resin (A) contains a binder resin (A1) and a binder resin (A2), the content of the binder resin (A1) is preferably 1 part by mass or more, more preferably 5 parts by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the binder resin (A2). The content of the binder resin (A1) is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less, based on 100 parts by mass of the binder resin (A2). When the content of the binder resin (A1) is within the above range, even if the initial resistance value is low, a conductive coating material is likely to be formed that can form a coating film in which the change in resistance value after expansion and contraction is small. The upper and lower limits of the content of the binder resin (A1) can be arbitrarily combined. For example, the content of the binder resin (A1) is preferably 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, and even more preferably 10 to 15 parts by mass, based on 100 parts by mass of the binder resin (A2).
[0042] The mass ratio (A+B) / C of the total content of the binder resin (A) and the crosslinking agent (B) to the content of the conductive filler (C) is 5 / 95 to 35 / 65, and preferably 10 / 90 to 25 / 75. If the mass ratio ((A+B) / C) is 5 / 95 or more, the change in the resistance value of the coating film after expansion and contraction is small. If the mass ratio ((A+B) / C) is 35 / 65 or less, the initial resistance value of the coating film can be kept low.
[0043] The total content of the binder resin (A), the crosslinking agent (B) and the conductive filler (C) is preferably 70 to 99.5 mass %, more preferably 80 to 98 mass %, and even more preferably 85 to 95 mass %, based on the total mass of the conductive coating material.
[0044] The content of carbon black (D) is 0.5 to 3.5 parts by mass, preferably 1.0 to 3.0 parts by mass, and more preferably 1.0 to 2.5 parts by mass, based on 100 parts by mass of the total content of the binder resin (A), the crosslinking agent (B), and the conductive filler (C). If the content of carbon black (D) is within the above range, even if the initial resistance value is low, the change in resistance value after stretching is small. That is, even if stretching is repeated, the rate of change in the resistance value of the coating film is small. In particular, if the content of carbon black (D) is equal to or greater than the above lower limit, the stretchability of the coating film is improved. If the content of carbon black (D) is equal to or less than the above upper limit, the film-forming property can be maintained good.
[0045] <Formula (1)> The conductive paint satisfies the following formula (1). DBP oil absorption × Wd / Wab≦130 (1) (In formula (1), "DBP oil absorption" is the dibutyl phthalate oil absorption of carbon black (D), "Wd" is the content of carbon black (D) relative to 100 parts by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C), and "Wab" is the total content of binder resin (A) and crosslinking agent (B) in 100% by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C).)
[0046] The ratio of DBP oil absorption × Wd / Wab is 130 or less, preferably 1 to 130, and more preferably 10 to 130. If the ratio of DBP oil absorption × Wd / Wab is less than the upper limit, even if the initial resistance is low, the change in resistance after stretching is small. That is, the rate of change in the resistance of the coating film is small even after repeated stretching. The reason for this is unclear, but it is thought to be as follows. DBP oil absorption × Wd / Wab of 130 or less means that the amount of carbon black (D) relative to the binder resin (A) and crosslinking agent (B) is appropriate. It is believed that the inclusion of an appropriate amount of carbon black (D) relative to the binder resin (A) and crosslinking agent (B) in the coating film gives the coating film appropriate rubber elasticity, making it less likely to crack, and thus reducing the change in resistance value after stretching. In addition, the contact between the conductive fillers (C) that are separated by the stretching of the coating film does not necessarily return to the same state as before stretching when the coating film shrinks to its original state, but it is believed that the carbon black (D) helps the contact between the conductive fillers (C), thereby ensuring a certain degree of conductivity. Dibutyl phthalate is a compound having two ester groups in the molecule. When the binder resin (A) has an ester group in the molecule, the DBP oil absorption of the carbon black (D) is particularly suitable as an indicator of the appropriate amount of carbon black (D) relative to the binder resin (A) and the crosslinking agent (B).
[0047] <Manufacturing method> The conductive coating material can be obtained by mixing the above-mentioned binder resin (A), crosslinking agent (B), conductive filler (C) and carbon black (D), and, if necessary, other components. For the mixing, a mixer such as a roll mill or a planetary mixer may be used.
[0048] <Action and effect> The conductive coating material of the present invention described above satisfies the above formula (1), contains the binder resin (A), the crosslinking agent (B), and the conductive filler (C) in a specific ratio, and also contains a specific amount of carbon black (D), so that even if the initial resistance value is low, a coating film with small change in resistance value after expansion and contraction can be formed. In other words, the coating film formed by the conductive coating material of the present invention has a small rate of change in resistance value even after repeated expansion and contraction, and is excellent in durability.
[0049] <Application> The conductive paint of the present invention can be used for circuits of electronic components, etc. Specifically, the conductive paint of the present invention can be used for touch panel circuits, flexible substrates, wearable devices, etc. In particular, the conductive paint of the present invention is suitable for applications requiring flexibility and stretchability.
[0050] The coating film can be obtained, for example, by applying the conductive coating material of the present invention onto a substrate and drying it. For example, when the conductive paint contains at least a binder resin (A1) as the binder resin (A) and an isocyanate-based crosslinking agent as the crosslinking agent (B), when the conductive paint is applied to a substrate and dried to form a coating film, the polyol resin (A1) reacts with the isocyanate-based crosslinking agent by heating to generate a polyurethane resin, and a coating film containing the polyurethane resin, conductive filler (C) and carbon black (D), and other components as necessary, is obtained. The coating film thus obtained may contain a binder resin (A2).
[0051] The substrate is preferably flexible and stretchable. In particular, when the conductive coating material contains a polyurethane resin as the binder resin (A), or when the conductive coating material contains a binder resin (A1) as the binder resin (A) and an isocyanate-based crosslinking agent as the crosslinking agent (B), the substrate is preferably made of a urethane resin from the viewpoint of excellent adhesion to the coating film.
[0052] [Printed wiring board] The printed wiring board of the present invention is formed by forming a circuit on an insulating substrate with a coating film (also called a "conductive coating film") obtained by using the conductive coating material of the present invention described above. That is, the printed circuit board has an insulating substrate and a circuit formed on the insulating substrate, and the circuit is formed by using the conductive coating material of the present invention.
[0053] As the insulating substrate, any of the conventionally known substrates used as wiring boards can be used, including, for example, substrates made of inorganic materials such as glass substrates, ceramic substrates, and silicon substrates; and substrates made of organic materials. Examples of organic materials include polyesters such as polyethylene terephthalate and polyethylene naphthalate, silicones such as polydimethylsiloxane, polydiphenylpolysiloxane and polyfluorosiloxane, urethanes such as thermoplastic polyurethane elastomers, polyimides, polyphenylene sulfide, polyolefins such as polyethylene and polypropylene, polyamides, polystyrene, acrylics, polyvinyl alcohol, ethylene propylene diene, and epoxies. Among these, the use of an insulating substrate containing unreacted monomers such as urethane improves the adhesion of the coating film formed from the conductive paint.
[0054] The thickness of the insulating substrate may be appropriately set depending on the application of the printed wiring board, and is preferably, for example, 20 to 600 μm. If the thickness of the insulating substrate is within the above range, the printed wiring board tends to have good elasticity and durability.
[0055] The method for forming a circuit on an insulating substrate is not particularly limited, but an example of such a method includes applying the conductive paint of the present invention to an insulating substrate so as to form a desired circuit pattern, and then drying the coating to form a circuit made of a coating film. That is, one embodiment of a method for manufacturing a printed wiring board includes a pattern forming step of applying the conductive paint of the present invention onto an insulating substrate to form a circuit pattern, and a drying step of drying the circuit pattern.
[0056] Examples of methods for applying the conductive paint include screen printing, gravure printing, offset printing, roll coating, and bar coating. The drying temperature is preferably, for example, 70 to 160°C. The drying time is preferably, for example, 2 to 60 minutes. EXAMPLES
[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. It should be noted that Example 11 is a reference example. The materials used in each example are as follows:
[0058] [material] Resin A1-1: Polyester polyol (manufactured by Kuraray Co., Ltd., product name "Kuraray Polyol P-2010", hydroxyl value 56 mg KOH / g, weight average molecular weight 2,000, glass transition temperature -66.6°C). Resin A1-2: Polyester polyol (manufactured by Kuraray Co., Ltd., product name "Kuraray Polyol P-510", hydroxyl value 224 mg KOH / g, weight average molecular weight 500, glass transition temperature -76.7°C). Resin A1-3: Polyester polyol (manufactured by Kuraray Co., Ltd., product name "Kuraray Polyol P-6010", hydroxyl value 18.8 mg KOH / g, weight average molecular weight 6,000, glass transition temperature -64.3°C). Resin A1-4: Polyhydric alcohol (manufactured by Kuraray Co., Ltd., product name "MPD (3-methyl-1,5-pentanediol)", hydroxyl value 950.8 mg KOH / g, weight average molecular weight 118). Resin A1-5: Polycaprolactone polyol (manufactured by Perstorp, product name "Capa 2803", hydroxyl value 14 mg KOH / g, weight average molecular weight 8,000). Resin A2-1: Polyester resin (manufactured by Unitika Ltd., product name "Elitter UE-3223", hydroxyl value 6 mg KOH / g, weight average molecular weight 22,000, glass transition temperature 4°C). Resin A2-2: Polyester resin (manufactured by Unitika Ltd., product name "Elitel UE-9100", hydroxyl value 2 mg KOH / g, weight average molecular weight 30,000, glass transition temperature 18°C). Isocyanate compound (B1): hexamethylene diisocyanate (Asahi Kasei Corporation, product name "Duranate E402-B80B", pure content 80% by mass). Conductive filler (C1): Ames Advanced Materials Corporation, product name "Silver Powder SPS", average particle size 3 μm, irregular silver powder. Conductive filler (C2): Ames Advanced Materials Corporation, product name "SF-70M", average particle size 2 μm, flake silver powder. Carbon black (D1): Manufactured by Orion Engineered Carbons SA, product name "Printex XE-2B", DBP oil absorption 420ml / 100g. Carbon black (D2): Manufactured by Orion Engineered Carbons SA, product name "Printex L6", DBP oil absorption 123 ml / 100 g. · Solvent: Isophorone.
[0059] [Examples 1 to 15, Comparative Examples 1 to 6] <Preparation of conductive paint> According to the formulations shown in Tables 1 to 4, the binder resin (A), the crosslinking agent (B), the conductive filler (C), the carbon black (D), and the solvent were mixed together to obtain a conductive coating material. Note that blanks in Tables 1 to 4 indicate that the component is not blended. "DBP oil absorption" in Tables 1 to 4 is the DBP oil absorption of carbon black (D). "Wd" is the content of carbon black (D) per 100 parts by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C). "Wab" is the total content of binder resin (A) and crosslinking agent (B) per 100% by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C). In addition, in Tables 1 to 4, the total amounts are rounded off to one decimal place.
[0060] <Preparation of test specimen> The conductive paint was applied by screen printing to a pattern of 1 mm width, 50 mm length and 20 μm thickness on a substrate made of a urethane sheet with a width of 15 mm, a length of 70 mm and a thickness of 100 μm.Then, it was dried and cured at 150°C for 30 minutes to prepare a test piece with a circuit pattern formed of a coating film made of the conductive paint on the substrate. The test pieces thus obtained were evaluated for the rate of change in resistance value as follows.
[0061] <Evaluation of the rate of change in resistance value> The electrical resistance value between both ends of the circuit pattern in the longitudinal direction was measured with a digital multimeter (manufactured by ADC Corporation), and this was taken as the "initial resistance value." Next, the circuit pattern with an initial length of 50 mm was stretched to 60 mm, and then returned to the initial length of 50 mm. This stretching was repeated 100 times at a stretching speed of 500 mm / min, and a resistance change test was performed. After that, the electrical resistance between both ends of the circuit pattern in the longitudinal direction was measured, and this was defined as the "resistance value after 100 stretches." The rate of change in resistance value was calculated from the following formula (2) and evaluated according to the following criteria. The results are shown in Tables 1 to 4. ◎, ◯, and △ are considered to be acceptable. In Tables 1 to 4, the rate of change in resistance value is rounded off to the first decimal place. Resistance change rate [%] = (resistance after 100 stretches – initial resistance) / initial resistance × 100 (2)
[0062] (Evaluation Criteria) ⊚: The rate of change in resistance value is 860% or less (particularly good). ◯: The rate of change in resistance value is more than 860% and 900% or less (good). △: The rate of change in resistance value is over 900% and is 1000% or less (practical). ×: The rate of change in resistance value is more than 1000% (defective).
[0063] <Evaluation of initial adhesion> Test pieces were prepared by applying Nichiban Co., Ltd.'s Cellotape (registered trademark) in parallel at intervals of approximately 2 cm to a copper-clad substrate, placing the conductive paint of each example between the tapes, rubbing with a glass rod, and curing at 150°C for 30 minutes. The obtained test piece was cut with a cutter knife in 11 parallel lines at intervals of 1 mm±0.1 mm, reaching the copper-clad portion of the copper-clad substrate, to produce 100 1 mm square grids. Cellotape (registered trademark) manufactured by Nichiban Co., Ltd. was applied to the grids by pressing it with a fingernail so as not to trap air bubbles, and one end of the Cellotape (registered trademark) was held and pulled in one go in a direction perpendicular to the substrate to remove the Cellotape (registered trademark) from the test piece. The number of grids of the coating film remaining on the test piece after peeling was counted and evaluated according to the following criteria. (Evaluation Criteria) ◯: 90 or more grid marks remain on the test piece. △: The number of grid lines remaining on the test piece was 80 to 89. ×: The number of cross-cut marks remaining on the test piece is 79 or less.
[0064] [Table 1]
[0065] [Table 2]
[0066] [Table 3]
[0067] [Table 4]
[0068] The conductive paints obtained in each Example were able to form coating films with small changes in resistance after expansion and contraction even when the initial resistance was low. In addition, the initial adhesion of the coating film to the substrate was excellent. In contrast, the coating films formed from the conductive paints of Comparative Examples 1 and 2, in which the content of carbon black (D) was 0.2 parts by mass or 4.0 parts by mass per 100 parts by mass of the total content of the binder resin (A), crosslinking agent (B), and conductive filler (C), showed a large change in resistance value due to repeated expansion and contraction. The coating film formed from the conductive paint of Comparative Example 3, in which DBP oil absorption amount×Wd / Wab exceeded 130, showed a large change in resistance value due to repeated expansion and contraction. The coating film formed from the conductive coating material of Comparative Example 4, which did not contain carbon black (D), showed a large change in resistance value due to repeated expansion and contraction. The coating films formed from the conductive coating materials of Comparative Examples 5 and 6, in which the binder resin (A) did not contain a resin having a weight average molecular weight of 200 to 7,000, showed a large change in resistance value due to repeated expansion and contraction.
Claims
1. A binder resin (A), a crosslinking agent (B), carbon black (D), and a conductive filler (C) other than the carbon black (D), the carbon black (D) has a dibutyl phthalate oil absorption of 100 to 600 ml / 100 g; the binder resin (A) is composed only of a binder resin (A1) and a binder resin (A2), the binder resin (A1) is a polyol resin having a weight average molecular weight of 200 to 7,000, a hydroxyl value of 5 to 750 mgKOH / g, and a glass transition temperature of −100 to 0° C.; the binder resin (A2) is at least one selected from the group consisting of polyester resins and polyol resins having a weight average molecular weight of more than 7,000; (A+B) / C, which represents a mass ratio of the total content of the binder resin (A) and the crosslinking agent (B) to the content of the conductive filler (C), is 5 / 95 to 35 / 65; the content of the carbon black (D) is 0.5 to 3.5 parts by mass with respect to 100 parts by mass of the total content of the binder resin (A), the crosslinking agent (B), and the conductive filler (C); A conductive paint that satisfies the following formula (1). DBP oil absorption x Wd / Wab≦130 (1) (In formula (1), "DBP oil absorption" is the dibutyl phthalate oil absorption of carbon black (D), "Wd" is the content of carbon black (D) relative to 100 parts by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C), and "Wab" is the total content of binder resin (A) and crosslinking agent (B) in 100% by mass of the total content of binder resin (A), crosslinking agent (B), and conductive filler (C).)
2. 2. A printed wiring board comprising an insulating substrate and a circuit formed thereon by a coating film obtained by using the conductive coating material according to claim 1.
Citation Information
Patent Citations
Conductive paste
JP2005078967A
Conductive paste and printed circuit using the same
JP2006260818A
Conductive paste and wiring board using the same
JP2007066824A
Conductive member with elastic wiring
JP2012054192A
Conductive composition, conductive composition sheet, conductive substrate, collector sheet, wiring circuit board, fuel battery, and manufacturing method of conductive composition
JP2013164984A